Effectiveness of Red Velvet as Brand Ambassadors for Azarine Cosmetic in Makeup Series Products - Victoria Amijaya; Inri Inggrit Indrayani; Felicia Goenawan (Petra Christian University, 2025)
Marketing Public Relations was an activity aimed at creating a positive image. A brand ambassador was someone who functioned as a representation or face of a brand. The use of famous celebrities as brand ambassadors during the launch of new products significantly increased public appeal and attention. Red Velvet was a South Korean girl group that has been active in the music industry for 10 years since their debut in 2014. Azarine Cosmetic appointed Red Velvet as the brand ambassador. This research aimed to measure the effectiveness of Red Velvet as the brand ambassador for Azarine Cosmetic's makeup series. The research approach was descriptive quantitative, with data collection techniques using an online questionnaire method through Google Forms distributed to 100 respondents using a Likert scale. The sampling technique employed purposive sampling. This study measured the effectiveness of the brand ambassador using Hovland's (1953) source credibility theory, which was divided into three indicators: trustworthiness, attractiveness, and expertise. The research results indicated that Red Velvet, as the brand ambassador for Azarine Cosmetic's, was deemed effective according to the source credibility theory, with expertise being the highest indicator because Red Velvet possessed a strong charm as a brand ambassador for the makeup products.